Learning Object Repository Systems and Their Use in Greek Education - Analyti, Efi; Schoina, Ioanna; Travlou, Chrysi; Mitroyanni, Evangelia; Drongitis , Anastasios; Kriparopoulou, Antigoni (Technium Education and Humanities, 2024)
The article explores how modern information and communication technologies (ICT) enhance educational quality, emphasizing the importance of pedagogically sound applications to address the limitations of traditional educational systems. While ICT offers considerable benefits, such as increased engagement and support for collaborative learning, the integration of these technologies in education presents challenges, including disparities in access and shifts in learning methodologies. The concept of Open Educational Resources (OER) is highlighted as a transformative approach, allowing for the creation and sharing of diverse learning materials, which are crucial for promoting accessibility and equity in education. Additionally, the article discusses organizational development issues that schools face when implementing ICT, such as the need for adaptive school cultures, leadership support, and the alignment of school policies with ICT goals. It also presents examples of digital repositories and open educational resources, like Project Gutenberg, ERIC, and MIT OpenCourseWare, which provide free access to educational materials. In Greece, national projects have introduced digital literacy into the school community, with repositories such as Photodentro LOR and Helios, supporting the country's commitment to digital education aligned with the European Digital Agenda.